Le corps nu féminin et la censure dans trois films japonais : la beauté des détours - Patrice Bougon (Itinéraires)
Japanese culture can be considered as an art of the detour and ellipsis, according to Kûki Shûzo and Tanizaki Junichirô. The scope of this article is to analyse three films produced at a time when censorship was relatively strong. With Tales of the Moon and Rain (Ugetsu monogatari, 雨月物語) in 1953, by Mizoguchi Kenji, Manji (Svastika, 卍) and Tatouage (Irezumi, 刺青) in 1966, by Masumura Yasuzo, we analyse how rhetoric of eclipse suggests thanks to several techniques what the audience have to imagine and that is not shown on the screen.